Mary Pope Osborne's Magic tree house. the graphic novel / 3, Mummies in the morning - Laird, Jenny, 1969-; Laird, Jenny, 1969-; Matthews, Kelly (Comic book artist); Matthews, Nichole; Osborne, Mary Pope. (New York : Random House, 2022)
"The magic tree house has whisked Jack and Annie to ancient Egypt. Inside a pyramid, Jack and Annie find a long-dead queen who needs their help solving a centuries-old riddle. If only they can find their way through the pyramid's maze!"--
Keywords: Annie -- (Fictitious character from Osborne) -- Comic books, strips, etc; Jack -- (Fictitious character from Osborne) -- Comic books, strips, etc; Annie -- (Fictitious character from Osborne) -- Fiction; Jack -- (Fictitious character from Osborne) -- Fiction; Mummies -- Comic books, strips, etc; Pyramids -- Comic books, strips, etc; Riddles -- Comic books, strips, etc; Mummies -- Fiction; Pyramids -- Fiction; Riddles -- Fiction; Cartoons and comics; Egypt -- Comic books, strips, etc; Egypt -- Fiction; Fantasy comics; Graphic novels